In vitro evaluation of probiotic capability of acid lactic bacteria from guinea pig (Cavia porcellus) feces of an Experimental Center - Serrano, Carla (2021)
The present study evaluated the in vitro probiotic capacity of 150 lactic acid bacteria (BAL) isolated from feces of three breeds of guinea pigs from an Experimental Center of intensive rearing, by means of in vitro tests on agar that evaluated the capacity of amylolytic, proteolytic enzymatic activity, cellulolytic and antagonism against pathogenic Salmonella sp. The BAL strains that achieved a positive result in any of the in vitro tests were evaluated for survival at pH 2.0, 4.0 and 0.3% bile. Gram positive strains were obtained, 93.3% of them with bacillary morphology and6.7% with ovoid morphology. 38.7% of strains showed the ability to degrade soluble starch, 66.7% for milk proteins and 4% for sodium carboxymethyl cellulose. Only 5.3% of strains had an antagonistic action against Salmonella sp. The frequency of strains according to race in relation to amylolytic and proteolytic degradation proved to have a significant statistical association. The survival capacity of the strains evaluated by each breed is also highlighted, where a frequency greater than 40% was obtained in each trial. The probiotic potential of native BAL isolated from feces of guinea pigs that would be evaluated in future field trials is highlighted.